(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
A class of n-order (F,a,p, d)-convex function and their generalization on functions is introduced. Using the assumption on the functions involved,weak, strong ,and converse duality theorems are established for the n-order dual problem